Restriction of virus movement into axillary buds is an important aspect of resistance in cassava to African cassava mosaic virus - Ogbe, F.; Dixon, A.G.O.; Thottappilly, G.; Atiri, G.I. (Wiley, 2002)
Axillary buds and bark samples of resistant, moderately resistant and susceptible (control) cassava genotypes either naturally infected under field conditions or experimentally inoculated by grafting were indexed for African cassava mosaic virus (ACMV). Virus detection was carried out using enzyme‐linked immunosorbent assay and polymerase chain reactions to determine the distribution of the virus within the plant and elucidate the genotypes response to virus movement. Significantly more bud and bark samples were positive for virus on the susceptible genotype TME 117 than resistant genotypes TMS 30001 and TMS 91/02319, or the moderately resistant genotype TMS 30572. Detectable virus concentration was significantly lower in the buds of moderately resistant and resistant genotypes than the susceptible control. Under field conditions, it was significant that more primary stem buds were infected than the buds of secondary and tertiary stems but such a gradient was not obvious with bark samples. Shoots that had asymptomic new leaves after the initial symptomatic leaves had no virus in their buds, but some of the bark samples from the same plants tested positive. A significant interaction was observed between year and stem type, and among year, genotype and stem type with respect to virus detection in bud and bark samples. Restriction of virus movement into axillary buds occurred in all the resistant and moderately resistant genotypes. This may explain ACMV‐infected stem cuttings of resistant genotypes producing healthy plants in subsequent generation.